Using Cultural Narratives to Enhance Identity and Tolerance in Multicultural Classrooms - Firmansyah Yunialfi Alfian; Ary Meizari Alfian; Ita Fionita (Yayasan Adra Karima Hubbi, 2026)
Background. Multicultural classrooms present both opportunities and challenges in fostering inclusive identities and tolerance among students from diverse cultural backgrounds. While educational systems are increasingly expected to promote social cohesion, conventional instructional approaches often emphasize cognitive knowledge of diversity over affective engagement. This gap is urgent, as rising social polarization and ethnic fragmentation in globalized societies demand pedagogical interventions that go beyond superficial diversity awareness to address deep-seated identity negotiation. Purpose. This study aims to examine the effectiveness of using cultural narratives as a pedagogical strategy to enhance students’ identity awareness and tolerance. By exploring narrative engagement, this research provides a practical framework for educators to solve the broader problem of social exclusion and prejudice in diverse school environments. Method. The research investigates whether structured narrative engagement can influence both attitudinal and relational dimensions of cross-cultural competence. A mixed-methods quasi-experimental design was implemented involving 120 secondary school students divided into experimental and control groups. Results. Findings indicate statistically significant improvements in tolerance levels and identity clarity among students exposed to cultural narratives (p < 0.05). Qualitative data reveal increased empathy and reduced stereotypical perceptions. Conclusion. The study concludes that cultural narratives constitute an effective, evidence-based approach for strengthening inclusive identity formation and promoting tolerance in multicultural educational settings.